Menghubungkan Digital Leadership dengan Work Engagement melalui Digital Readiness: UMKM Industri Kreatif di Keresidenan Kedu, jawa tengah - Wening, Nur; Sujoko, Sujoko (ICON Publisher, 2025)
This study explores the influence of digital leadership on employee work engagement within creative MSMEs in the Kedu Residency, with a particular focus on digital readiness as a mediating factor. The rapid advancement of digital technology poses significant challenges for MSMEs, necessitating effective leadership to enhance workforce engagement. Employing a quantitative approach, data were collected from 200 respondents using purposive sampling. Analysis was conducted through regression techniques and the Sobel test to assess the relationships among digital leadership, digital readiness, and work engagement. The findings reveal that digital leadership has a positive influence on digital readiness, which in turn significantly boosts employee work engagement. However, the direct effect of digital leadership on engagement was found to be negative when digital readiness among employees was insufficient. These results underscore the importance of enhancing digital readiness to fully leverage the benefits of digital leadership in increasing employee engagement. This research offers valuable insights for MSME owners aiming to improve workforce adaptability and engagement in the digital era.